Impacts of Whole-Body Vibration on Muscle Strength, Power, and Endurance in Older Adults: A Systematic Review and Meta-Analysis - Gonçalves de Oliveira, Raphael; Coutinho, Heloísa Maria Elaine Licha; Martins, Maiara Naldi Mansano; Bernardo-Filho, Mario; de Sá-Caputo, Danúbia da Cunha; Campos de Oliveira, Laís; Taiar, Redha (Journal of Clinical Medicine, 2023)
Background: Randomized clinical trials (RCTs) were conducted to identify the effectiveness of whole-body vibration (WBV) on strength, power, and muscular endurance in older adults. However, the results of different studies are contradictory. Objective: To verify the impacts of the WBV on strength, power, and muscular endurance in older adults. Methods: The search was carried out in PubMed, Embase, CENTRAL, CINAHL, SPORTDiscus, Web of Science, LILACS and PEDro databases. Methodological quality was assessed using the PEdro scale. Meta-analysis calculations were performed using the standardized mean difference, comparing WBV with control groups and WBV with other types of exercise. Results: Thirty-four studies were included in the current systematic review. Most studies (56%) had low methodological quality (PEDro score < 6). WBV, compared with control groups, has significant effects on muscle strength of knee extensors and flexors, lower limb extensors, and ankle plantar flexors. There were no differences between WBV and other types of exercise. Subgroup analyzes demonstrated that, in general, the significant results observed in the primary analyzes were not dependent on body position during vibration, kind of vibration, cumulative dose or magnitude of WBV. Conclusion: WBV was effective in increasing lower limb muscle strength. However, no significant results were observed for upper limb strength, lower limb power, and lower and upper limb muscle endurance in older adults. However, more studies are needed to better understand the physiological impacts of WBV in older.
Number: 13
Keywords: exercise; mechanical vibration; musculoskeletal fitness